Effect of pregnancy induced hypertension on maternal and perinatal outcome at tertiary care center in Ahmedabad, Gujarat, India - Parmar, Meghavini R.; Vaja, Pradhyuman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy is a physiological event for utmost women. Almost 20% - 30% of the adult population and more than 5% - 8% of all pregnancies in the world suffered from hypertension (HTN) and 5% - 22% of all pregnancies have develop some kind of medical problem due to hypertensive. To study the prevalence of PIH and to find out the association of PIH with perinatal and maternal outcome. Methods: Prospective study was done among 110 cases of PIH admitted at department of obstetrics and Gynecology in B.J. Medical college, Ahmedabad during July 2005 to July 2007. Hypertension was identified based on the definition by the Australian Society of the Study of Hypertension in Pregnancy and that of the Working Group Report on High Blood Pressure in Pregnancy, which establish blood pressure levels > 140/90 mmHg or hypertension diagnosis marked on the record. Results: Almost 44% participants had mild PIH and 56% had severe PIH. Almost 32% participants had grade I changes and 29% had grade II changes. Low birth weight was found in 53% baby. Maternal complication observed in 16% participants. Out of 16 patients, highest incidence of eclampsia was observed followed by APH, DIC respectively. One incidence of maternal death also occurred. Perinatal complications were observed in 46% cases which include IUGR (60.9%), birth asphyxia (8.7%), RDS (4.3%) and perinatal death (15.2%) respectively. Conclusions: Pregnancy-induced hypertension is associated with multiple complications in the mother and baby, and particularly preterm delivery. Timely intervention of regular ANC check-up, nutrition, health education etc. can reduce the severity of PIH which lead to decrease in maternal and perinatal complications.